Multiple Climate States of Habitable Exoplanets: The Role of Obliquity and Irradiance - Kilic, Cevahir; Raible, Christoph; Stocker, Thomas (The Astrophysical Journal, 2017)
Stable, steady climate states on an Earth-size planet with no continents are determined as a function of the tilt of the planet's rotation axis (obliquity) and stellar irradiance. Using a general circulation model of the atmosphere coupled to a slab ocean and a thermodynamic sea ice model, two states, the Aquaplanet and the Cryoplanet, are found for high and low stellar irradiance, respectively. In addition, four stable states with seasonally and perennially open water are discovered if comprehensively exploring a parameter space of obliquity from 0° to 90° and stellar irradiance from 70% to 135% of the present-day solar constant. Within 11% of today's solar irradiance, we find a rich structure of stable states that extends the area of habitability considerably. For the same set of parameters, different stable states result if simulations are initialized from an aquaplanet or a cryoplanet state. This demonstrates the possibility of multiple equilibria, hysteresis, and potentially rapid climate change in response to small changes in the orbital parameters. The dynamics of the atmosphere of an aquaplanet or a cryoplanet state is investigated for similar values of obliquity and stellar irradiance. The atmospheric circulation substantially differs in the two states owing to the relative strength of the primary drivers of the meridional transport of heat and momentum. At 90° obliquity and present-day solar constant, the atmospheric dynamics of an Aquaplanet state and one with an equatorial ice cover is analyzed.